2011
DOI: 10.1111/j.1865-1682.2011.01260.x
|View full text |Cite
|
Sign up to set email alerts
|

First Evidence of Peste des Petits Ruminants (PPR) Virus Circulation in Algeria (Sahrawi Territories): Outbreak Investigation and Virus Lineage Identification

Abstract: Following reports of increased mortality in the small ruminant population of the Sahrawi territories, western Algeria, between January and May 2010, local veterinary authorities suspected an outbreak of peste des petits ruminants (PPR). An investigation was implemented in May 2010 and followed up in October 2010 in the Sahrawi refugee camps, Tindouf province, with the objective of confirming the circulation of the peste des petits ruminants virus (PPRV). Laboratory results confirmed the presence of PPRV in 33.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
41
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 9 publications
1
41
0
Order By: Relevance
“…PPR viruses belonging to lineages I and II have been isolated exclusively from west and central African countries including the Ivory Coast, where the PPR virus was first detected in the 1940s (Chard et al, 2008;Luka et al, 2011;Munir et al, 2012b). Lineage III has been isolated from eastern Africa and the Arabian peninsula (Shaila et al, 1996;Kwiatek et al, 2011); lineage IV has been isolated in Asia (Kwiatek et al, 2007;Kerur et al, 2008;Wang et al, 2009;Balamurugan et al, 2010;Munir et al, 2012a;Anees et al, 2013), in the Middle East (Esmaelizad et al, 2011), and more recently in northern Africa (Sanz-Alvarez et al, 2008;Kwiatek et al, 2011;De Nardi et al, 2012 locations 5737-5761 and 6184-6160, respectively (Özkul et al, 2002). The RT-PCR reaction was performed with a 1-step RT-PCR kit (QIAGEN) in a final volume of 20 µL, which contained 4 µL of 5X 1-step RT-PCR buffer, 0.4 µM of each primer, 0.8 µL of 10 mM of each dNTP, 0.8 µL enzyme mix, 4 µL of 5X Q solution, 7 µL of PCR-grade water, and 2.6 µL of sample RNA.…”
Section: Introductionmentioning
confidence: 99%
“…PPR viruses belonging to lineages I and II have been isolated exclusively from west and central African countries including the Ivory Coast, where the PPR virus was first detected in the 1940s (Chard et al, 2008;Luka et al, 2011;Munir et al, 2012b). Lineage III has been isolated from eastern Africa and the Arabian peninsula (Shaila et al, 1996;Kwiatek et al, 2011); lineage IV has been isolated in Asia (Kwiatek et al, 2007;Kerur et al, 2008;Wang et al, 2009;Balamurugan et al, 2010;Munir et al, 2012a;Anees et al, 2013), in the Middle East (Esmaelizad et al, 2011), and more recently in northern Africa (Sanz-Alvarez et al, 2008;Kwiatek et al, 2011;De Nardi et al, 2012 locations 5737-5761 and 6184-6160, respectively (Özkul et al, 2002). The RT-PCR reaction was performed with a 1-step RT-PCR kit (QIAGEN) in a final volume of 20 µL, which contained 4 µL of 5X 1-step RT-PCR buffer, 0.4 µM of each primer, 0.8 µL of 10 mM of each dNTP, 0.8 µL enzyme mix, 4 µL of 5X Q solution, 7 µL of PCR-grade water, and 2.6 µL of sample RNA.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, retrospective surveys on a Moroccan serological bank could not detect PPRV antibodies in small ruminant sera collected before 2008 (Ettair, 2012). The results of the molecular studies in each country show that the lineage IV of PPRV is circulating throughout the sub-region (Abd et al, 2010;De Nardi et al, 2012;Sghaier et al, 2014;Kardjadj et al, 2015a) except Mauritania, where El Arbi et al (2014) reported the presence of the lineage II, therefore, highlighting the existence of a second lineage circulating in North Africa.…”
Section: Molecular Epidemiology Of Ppr In Algeriamentioning
confidence: 98%
“…In 2011, PPR was reported in Sahrawi refugee camps in Tindouf district, at the south western border of Algeria with Western Sahara, Mauritania, and Morocco and the sequence analysis clustered the circulating virus under lineage IV of PPRV (De Nardi et al, 2012). A year later, Kardjadj et al (2015a) described the first serological and molecular typing of the PPRV strain implicated in an outbreak in Ghardaïa district, in the center of Algeria.…”
Section: Molecular Epidemiology Of Ppr In Algeriamentioning
confidence: 99%
“…In 2011, PPR was reported in Sahrawi refugee camps in Tindouf district, at the southwestern border of Algeria with Western Sahara, Mauritania, and Morocco and the sequenced analysis clustered the circulating virus under lineage IV of PPRV (De Nardi et al 2011). However, the epidemiology of PPRV in Algeria is not well understood.…”
Section: Introductionmentioning
confidence: 97%